Solid Variant of Aneurysmal Bone Cyst of the Left Parietal Bone without Preceding Trauma - Nestler, Ulf; Wagner, Hans-Joachim; Schaenzer, Anne; Preuss, Matthias (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Introduction We report the case of a 17-year-old girl with an indolent, smooth swelling of the left cranial vault that had been developing for 2 months. Complete surgical excision was performed and the defect was closed using artificial bone cement. The integrity of the dura mater was conserved and the patient recovered without neurological deficit. Magnetic resonance imaging (MRI) controls 6 and 18 months after the operation did not find signs of recurrence.Results The lesion consisted of an elastic bone shell containing bony trabeculae with soft brown-greyish tissue and posthemorrhagic dark fluid. Histological assessment found CD68 positive multinucleated giant cells in a highly cellular fibroblastic matrix surrounding bony lamellar structures, without signs of inflammation or malignancy. Hyperparathyroidism was ruled out by normal serum values for parathyroid hormone, calcium, phosphate, and alkaline phosphatase. Histologically, first diagnosis was giant cell reparative granuloma and reference pathology disclosed aneurysmal bone cyst.Conclusions The solid variant of aneurysmal bone cyst and the giant cell reparative granuloma can be histologically indistinguishable. Both lesions are only rarely encountered in cranial bones and most published cases affected the cranial base or the jaw, mainly in children or young adults. From a clinical point of view, classification into “outward” lesions (osteolysis of external parts of the vault with preservation of internal tabula) and “inward” lesions (intracranial multicystic lesions with raise of intracranial pressure) has been proposed. Three phases of development can be identified, and spontaneous involution has been described. Both entities are benign, but because in several cases an underlying malignant disease has been found, complete resection and regular follow-up by MRI are recommended.
Keywords: aneurysmal bone cyst; cranial vault; giant cell reparative granuloma; juvenile skull tumor